IMPROVEMENT OF EXECUTIVE POWER AS A MEANS TO OVERCOME CORRUPTION IN A HIGHER AUTHORITIES - Yuldashev, Sergey (Proceedings of National Aviation University (archive), 2016)
Purpose: The purpose of the article is a study of corruption at the level of ministries and departments, its origin and operation for later overcome, building organizational and management structure of the economy to meet the requirements of design-oriented development management. Methods: In this article applied the general principles and systemic and structural methods of constructing organizational structures both at the enterprise level and socio-economic systems as a whole. Results: Based on the conducted research it may be stated that Ukraine has overcome the elitist corruption at the level of ministries and agencies is essential to solving the problem of increasing the administrative capacity of the executive power. Substitution of ministries and agencies non-governmental structures will allow to overcome the existing system theft of a budget. Discussion: In the course of research substantiated, that there is no need to sustain those who are not able to realize themselves in socially useful areas - business, education (teachers, tutors, trainers), health (medical personnel), etc. Workers of these fields may be contained within the local budget, not central. And the most important thing is that the liquidation of the ministries and departments will be undermined by the preserved from the socialist era system of financial and material distribution, transformed into a system plundering of a budget.